Interactions between nitrogen fertilization and ozone in watermelon cultivar Reina de Corazones in open-top chambers. Effects on chlorophyll alpha fluorescence, lipid peroxidation, and yield - Calatayud, Ángeles; Pomares, Fernando; Barreno, Eva (2017)
Watermelon (Citrillus lanants) plants were grown for two consecutive years in open-top chambers with three different ozone concentrations (O-3-free air, O-3 ambient, and air with additional O-3; CFA, NFA, and NFA+O-3) and three nitrogen fertilizer concentrations [0, 14.0, and 29.6 g N per pot; N0, N1, and N2). There was an interaction between ozone and N fertilizer for the major parameters studied. O-3 and N2 treatments led to a significant decrease in maximum efficiency of photosystem 2 (PS2) photochemistry (F-v/F-m), and induced a significant decrease in the actual quantum yield of PS2 (Phi(PS2)), due mainly to the increased closure of PS2 reaction centres (q(P)) and to an increase in the non-photochemical quenching, (NPQ). On the other hand, these plants exhibited an increased susceptibility to photo inhibition, which could be associated with an increased fraction of reduced Q(A). An increase in lipid peroxidation indicated that damage was occurring at the membrane levels. High N concentration enhanced the detrimental effects of ozone on the fluorescence parameter induction and lipid peroxidation. All these negative alterations led to a decreased yield.